The Role of The Indonesian Language as a National Identity for Generation Z in Achieving National Resilience - Prismadianto, Gita; Endrawati, Lucky; Putra, Fadillah; Susilo Putri, Widyarini (Wacana Journal of Social and Humanity Studies, 2026)
This study examines the impact of slang and foreign language use on national resilience, particularly among Generation Z, who are influenced by globalization and digitalization. It focuses on discourse patterns on social media, the influence of foreign languages on perceptions of Indonesian Language, and factors hindering the younger generation’s awareness of the importance of standard Indonesian. A qualitative approach with a phenomenological design was used, and primary data were collected through interviews, observations, and FGDs in Malang. Data validity was ensured through triangulation, member checking, and an audit trail. The data were analyzed using an interactive model that included data reduction, data display, and conclusion drawing and verification. The results show that Generation Z employs a variety of conversational styles, ranging from slang to informative exchanges that involve code-switching between the Indonesian Language and foreign languages. This indicates both the influence of global culture and globalization, as well as the threat to the use of the standard Indonesian Language as a symbol of national identity. Although Generation Z is likely to find standard language increasingly irrelevant in informal communication, they continue to find it relevant in formal communication. In conclusion, measures involving formal education, digital literacy programs, and community support are necessary to maintain the Indonesian Language as a symbol of national identity. Keywords: Indonesian Language, Pillar of Identity, Generation Z, Globalization, National Resilience